DETEKSI MIKROFILARIA WUCHERERIA BRANCROFTI DAN BRUGIA SP PADA SPESIES NYAMUK PASCA PEMBERIAN OBAT PENCEGAHAN MASSAL (POPM) DI BEBERAPA KABUPATEN DI INDONESIA - Jusniar Ariati; Dian Perwitasari; Roy Nusa RES; Rina Marina; Pei-Yu Alison Lee (Puslitbang Upaya Kesehatan Masyarakat, 2020)
ABSTRACT Efforts to break transmission of filariasis chain, through elimination program with preventive mass drug administration (POPM) and vector control, which is currently taking place in all provinces in Indonesia. Known as elephantiasis or lymphatic filariasis, it is a filarial worm with the main species being Wuchereria bancrofti and Brugia sp. The aims of study was to identify mosquitoes that have the potential become vector filariasis. Known as elephantiasis (Elephantiasis) or Lymphatic filariasis is a major species of filarial worms with that Wuchereria bancrofti and Brugia sp. Mosquito collection conducted in 23 districts / cities in Indonesia using modificated Human Landing Collection (HLC) method that is double net to feed humans inside, while the method of Transcription Insulated Isothermal Polymerase Chain Reaction (iiPCR) was used to detect the presence of filarial worms in the mosquitoes. The number of samples collected was 26,276 mosquitoes, 38 were identified. The results of the examination used iiPCR showed that positive W. bancrofti was found in 6 districts / cities and positive Brugia sp were found in 9 districts / cities where the study was conducted. There are other mosquito species that are not confirmed as filarial vectors, but found DNA traces both the parasite in mosquitoes that have not been confirmed as vectors. Keywords: Microfilariae, Wulcheria brancrofti, Brugia malayi, Mass Drug Administration (MDA) ABSTRAK Upaya pemutusan rantai penularan filariasis melalui program eliminasi dengan pemberian obat pencegahan masal (POPM) dan pengendalian vector, saat ini sedang berlangsung di semua provinsi di Indonesia. Di kenal sebagai penyakit kaki gajah (Elephantiasis) atau Filariasis limfatik merupakan cacing filaria dengan spesies utama yaitu Wuchereria bancrofti, dan Brugia sp. Penelitian ini bertujuan untuk mengetahui nyamuk yang berpotensi menjadi vector filariasis. Pengambilan sampel nyamuk dilakukan di 23 kabupaten/kota di Indonesia menggunakan metode Modificated Human Landing Collection (HLC) yaitu kelambu ganda dengan umpan manusia, sedangkan metode Transcription Insulated Isothermal Polimerase Chain Reaction (iiPCR) digunakan untuk mendeteksi keberadaan cacing filaria dalam tubuh nyamuk. Jumlah nyamuk yang berhasil dikumpulkan sebanyak 26.276 nyamuk dengan 38 spesies yang teridentifikasi. Hasil pemeriksaan DNA menggunakan iiPCR menunjukkan spesies Wulchereria bancrofti ditemukan di 6 kab/kota dan spesies Brugia malayi ditemukan di 9 kab/kota tempat penelitian. Terdapat spesies nyamuk lainnya yang tidak terkonfirmasi sebagai vektor filaria, namun ditemukan jejak DNA kedua parasite tersebut dalam nyamuk yang belum terkonfirmasi sebagai vektor. Kata kunci: Mikrofilaria, Wulcheria brancrofti, Brugia malayi, POPM